2004
DOI: 10.1002/ana.20090
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of von Hippel–Lindau gene deficiency

Abstract: The histogenetic origin and the basis of the distribution of central nervous system (CNS) hemangioblastomas in the von Hippel-Lindau (VHL) tumor suppressor gene syndrome, VHL disease, are unknown. To better understand hemangioblastoma histogenesis, we analyzed postmortem CNS tissues from four patients with well-established diagnosis of VHL disease including development of characteristic tumors and positive family history. Numerous angiomesenchymal tumorlets, which resembled hemangioblastoma, but which also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 10 publications
4
52
0
Order By: Relevance
“…Expression of Epo is secondary to VHL gene deficiency, 15,16 whereas EpoR expression normally occurs in development as part of a response to hypoxia. 11,12 With inactivation of VHL protein in cells, however, Epo and EpoR coexpression persists in tumor precursor cells. 11,12 Retention of Epo and EpoR coexpression may lead to cell proliferation via autocrine stimulation, which appears to be an essential step in renal carcinoma tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of Epo is secondary to VHL gene deficiency, 15,16 whereas EpoR expression normally occurs in development as part of a response to hypoxia. 11,12 With inactivation of VHL protein in cells, however, Epo and EpoR coexpression persists in tumor precursor cells. 11,12 Retention of Epo and EpoR coexpression may lead to cell proliferation via autocrine stimulation, which appears to be an essential step in renal carcinoma tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 With inactivation of VHL protein in cells, however, Epo and EpoR coexpression persists in tumor precursor cells. 11,12 Retention of Epo and EpoR coexpression may lead to cell proliferation via autocrine stimulation, which appears to be an essential step in renal carcinoma tumorigenesis. 24,25 There is evidence that in the kidney nephrogenous mesenchyme has a pluripotent capacity and gives rise to the renal epithelium, mesenchymal as well as stromal elements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to cerebellar hemangioblastomas affected VHL patients were found to have many angio-mesenchymal tumorlets in the dorsal nerve roots. As in NF2, loss of heterozygosity for the VHL gene was found already in the angio-mesenchymal lesions, suggesting that, (as in NF2) inactivation of the VHL wild type allele is necessary, but not sufficient for the formation of a symptomatic tumor 12 . The hypothesis that there are additional "hits" subsequent to the loss of NF2 allele in schwannomas was proposed by Woods et al 13 but very few schwannomas were found to have genomic alterations (amplifications or deletions) with comparative genomic hybridization 14 .…”
Section: Discussionmentioning
confidence: 94%